The Influence of The Project-Based Learning Model on Students' Creativity and Understanding of Science Concepts - Zaena Sultona Osi; Alauddin Shahih; Egi Gerhanandi; Kholid Khairul Umam (Indonesian Journal of Educational Innovation, 2025)
The importance of Project-Based Learning (PjBL) in learning lies in its ability to increase student engagement, develop various important skills, and make learning more meaningful. This study aims to investigate the effect of the Project-Based Learning (PjBL) model on the creativity and understanding of physics concepts among grade XI students. Involving 35 students studying Temperature and Heat material, this study used a one-group pretest-posttest design. Data were collected through a concept understanding test and a creativity questionnaire covering indicators of fluency, originality, flexibility, and elaboration. The results showed that the average value of concept understanding increased from 65 in the pretest to 82 in the posttest. Additionally, the creativity questionnaire revealed a significant increase in all aspects, with the average total creativity score rising from 70.5 to 85.5. These findings indicate that the implementation of the PjBL model not only improves students' concept understanding but also encourages their creativity. Therefore, the PjBL model is recommended as an effective method for enhancing student engagement and improving learning outcomes in physics education.